Islamic Ecotheology: Transcending Anthropocentrism through Wahdat al-Wujūd - Lohlker, Rüdiger (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2024)
The question addressed in this article is a possible new epistemological framework to find solutions to the current crisis. The analysis began with the idea of creation as a holistic concept. The problem discussed here is related to the relationship between transcendence and immanence. The discussion is based on the approach of Oneness or Unity of Being (wahdat al-wujūd) developed by Ibn ΄Arabī. This Sufi approach is supplemented by an outlook on modern scientific epistemologies. This article proposes a new epistemology based on the Oneness of Being, an outlook into the immanent thinking of the Deleuzian style, and modern scientific approaches, especially from advanced biology. Thus, this article attempts to overcome the problems arising from pre-modern thinking.